2018
DOI: 10.1182/blood-2018-01-826958
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic heterogeneity on baseline 18FDG-PET/CT scan is a predictor of outcome in primary mediastinal B-cell lymphoma

Abstract: An important unmet need in the management of primary mediastinal B-cell lymphoma (PMBCL) is to identify the patients for whom first-line therapy will fail to intervene before the lymphoma becomes refractory. High heterogeneity of intratumoral F-fluorodeoxyglucose (18FDG) uptake distribution on positron emission tomography/computed tomography (PET/CT) scans has been suggested as a possible marker of chemoresistance in solid tumors. In the present study, we investigated the prognostic value of metabolic heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 46 publications
5
59
0
Order By: Relevance
“…MH of the target lesion (ie, the lesion with the highest 18FDG uptake) was measured in each patient using the area under curve of cumulative SUV-volume histogram (AUC-CSH) method as previously published. 39…”
Section: Pet/ct Images Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…MH of the target lesion (ie, the lesion with the highest 18FDG uptake) was measured in each patient using the area under curve of cumulative SUV-volume histogram (AUC-CSH) method as previously published. 39…”
Section: Pet/ct Images Analysismentioning
confidence: 99%
“…34,36 In addition, metabolic heterogeneity (MH), a functional PET parameter with known prognostic value in solid tumors, 37,38 may also have a role in lymphomas. 39 Recent research provided preliminary but promising evidence that the integration of quantitative PET parameters with some clinical, biological, and molecular features may allow a more accurate prognostication in DLBCL. 29,40,41 The main aim of this study was to test the ability of baseline functional PET parameters in predicting the efficacy of immunochemotherapy in a cohort of DLBCL patients treated with R-CHOP14 in the prospective clinical trial SAKK 38/07.…”
Section: Introductionmentioning
confidence: 99%
“…Texture analysis can quantify the spatial pattern and arrangement of pixel intensities in medical images allowing to provide crucial information regarding tumor phenotype, thereby highlighting intratumor heterogeneity. Several works have demonstrated that this heterogeneity could have remarkable implications on tumor prognosis being a typical pattern of malignancies associated with aggressive behavior and poor response to therapies . In a recent study on 28 patients with NHL, De Paepe et al have demonstrated that first‐order ADC texture analysis on WB‐DWI‐MRI at 3T can increase the accuracy of lymph node characterization in comparison with ADC mean.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…1 Three years ago, in Blood, the authors introduced a new prognostic index for PMBCL, the total lesion glycolysis (TLG), which uses quantitative analysis of baseline 18FDG/positron emission tomography (PET). 2 The index was based on a series of 103 patients with PMBCL.…”
Section: Université René Descartesmentioning
confidence: 99%
“…1 The authors report that the presence of clonal interference, as defined by the presence of $2 signaling clones in a single patient sample, and not variant allelic frequency (VAF), was prognostic of inferior event-free survival, higher cumulative incidence of failure, and worse overall survival and was independent of older age, high white cell count, and the presence of a t(8; 21) cytogenetic abnormality (usually associated with poorer outcome within CBF AML).…”
Section: Prognosis Interfered With By Clonal Interferencementioning
confidence: 99%